Venus! : fierce and fabulous - McAnulty, Stacy (McAnulty, Stacy. Our universe., 2026)
"From writer Stacy McAnulty and illustrator Stevie Lewis, comes VENUS!-- a light-hearted nonfiction picture book about the sassiest member of our solar system"--